2020
DOI: 10.1096/fj.202000559r
|View full text |Cite
|
Sign up to set email alerts
|

Combining timed GDNF and ChABC gene therapy to promote long‐distance regeneration following ventral root avulsion and repair

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Similarly, although ChABC treatment does not enhance motoneuron survival, our distal ChABC treatment might have been more beneficial when applied more proximally at the reimplantation site (Figure 1E; Eggers et al, 2020). This was shown recently in a study delivering a peptide inhibiting CSPG signaling near the reimplanted nerve root (Li et al, 2015).…”
Section: Gene Therapy Treatment Locationsupporting
confidence: 63%
See 3 more Smart Citations
“…Similarly, although ChABC treatment does not enhance motoneuron survival, our distal ChABC treatment might have been more beneficial when applied more proximally at the reimplantation site (Figure 1E; Eggers et al, 2020). This was shown recently in a study delivering a peptide inhibiting CSPG signaling near the reimplanted nerve root (Li et al, 2015).…”
Section: Gene Therapy Treatment Locationsupporting
confidence: 63%
“…Regulating the duration of GDNF expression, could potentially overcome axonal coil formation. Although coil formation was attenuated significantly in our first study, with only incidental small isolated coils observed (Eggers et al, 2019b), in a second study increased coil formation was observed in 34% of the doxi-GDNF treated animals (Eggers et al, 2020). Between these studies, two differences exist which could underlie the observed coil development in the second study.…”
Section: Gdnf Treatment Concentration and Axonal Coil Formationmentioning
confidence: 50%
See 2 more Smart Citations
“…This approach, although technically challenging, constitutes an excellent lesion model closely mimicking the clinical situation of patients with brachial plexus injury, where regeneration takes months or even years (Eggers et al, 2019(Eggers et al, , 2020.…”
Section: Sciatic Nerve Injury Performed In Genetically Modified Micementioning
confidence: 99%